Anak Dalam Islam Perspektif Historis dan Sosiologis - Yusuf, Muhammad (Musawa Jurnal Studi Gender dan Islam, 2006)
This article focuses on children in Islam within historical and sociological perspectives. Children are the investment of both parent and society. They have to seriously take care of, shape, and develop the children's potentions. Historically, there was discrimination against woman children during the dark ages and, then Islam came and brought the idea of humanity and equality. The concept of humanity and equality places all children equally before God and society, in relation to their functions and roles. Infact, social, economic and cultural repression is the reason for the exploitation and violence against children.